The invasive blue crab Callinectes sapidus thermal response: Predicting metabolic suitability maps under future warming Mediterranean scenarios - Marchessaux, Guillaume; Bosch-Belmar, Mar; Cilenti, Lucrezia; Lago, Nicola; Mangano, Maria Cristina; Marsiglia, Nicoletta; Sarà, Gianluca (Frontiers in Marine Science, 2022)
One of the consequences of climate change and globalization is the recent proliferation of the invasive blue crab Callinectes sapidus in the Mediterranean Sea. In this study, C. sapidus thermal tolerance was investigated through experiments based on species metabolic response (measuring respiration rates). Thermal Performance Curve showed a CTmax at 40°C and an optimum at 24°C. Respiration rate increased between 12°C and 24°C and decreased until 30°C. At the highest temperatures (> to 30°C) a pointed increase in the respiration rate values was observed from 32°C before the organisms’ death at 40°C. Based on metabolic rates, Thermal Habitat Suitability (THS) maps were performed on current and futures temperature conditions in the Mediterranean Sea. The whole basin shows suitable conditions for population maintenances of C. sapidus in both current and future scenarios. The future scenarios show a mean increase of +0.2 of the THS over the year. The present study increases the understanding of the ecological performance and potential distribution of C. sapidus. This information will contribute to the design and implementation of risk assessment and management plans of this impactful crustacean in the Mediterranean Sea.